Geography Of Irrigation and Its Role in Agriculture Development in Vidarbha - Vithoba Dadve, Jagannath (Journal of Neonatal Surgery, 2025)
Irrigation occupies a very important role in agricultural development owing to physiographic and climatic diversity in the Vidarbha region that has recently been mugged by frequent drought, erratic monsoons, and uneven irrigation coverage, all making agricultural productivity and rural livelihoods susceptible to vagaries of nature. The research presents an analysis of the spatial distribution of irrigation infrastructure in Vidarbha and its impacts on cropping patterns, land use, and the economic viability of farming communities. The study identifies disparities in irrigation, evaluates various irrigation types, including canal, well, and micro-irrigation systems, concerning their efficiency, and uses district-level data and spatial mapping. The study suggests the formulation of region-specific irrigation policies coupled with integrated water resource management as a means to achieve fair and sustainable agricultural development. Strengthening irrigation infrastructure plus water use efficiency improvements could change the agrarian discourse to stop further distress and promote better agricultural production in the whole region...